Penurunan kadar BOD dan COD dalam limbah cair laundry menggunakan kombinasi adsorben alam sebagai media filtrasi - Meity Pungus; Septiany Christin Palilingan; Farly Tumimomor (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Laundry wastewater is generated in large quantities will pollute the environment such as rivers and soil if thrown away without any prior treatment. Laundry wastewater treatment methods that have been carried out are easy and inexpensive for household scale and have been proven to reduce levels of organic pollutants. Two parameters that can indicate the presence of organic pollutants in laundry wastewater are Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD). This study aims to determine the effect of the use of filtration media in the form of a combination of activated carbon adsorbent, zeolite, silica sand, anthracite and ferolite in reducing levels of BOD and COD in laundry wastewater. Based on the results of laboratory tests on the BOD and COD test parameters, it was found that after the filtration process there was a decrease in the BOD and COD levels in the laundry wastewater samples respectively by 53% and 54%. The results of the statistical analysis also showed that the presence of filtration treatment had a significant effect in reducing levels of BOD and COD in laundry wastewater samples. Thus, it can be concluded that the presence of filtration treatment is proven to significantly reduce BOD and COD levels which can also indicate decreased levels of organic pollutants contained in laundry wastewater.